Stigma Warna Kulit terhadap Standar Kecantikan di Kalangan Mahasiswa Prodi Tadris IPS UIN Mataram Tahun 2023 - Alif Ilman Mansyur; Raohun Sapitri; Fidlawati Fidlawati (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2023)
Currently, beauty standards are still being discussed among the public. The emergence of stigma or the view that beaty must have white skin, tall, thin body, sharp nose, and so on. This emerging stigma then encourages society, specially women, to then compete to have white skin. The emergence of views about the standard of beaty must be white, this appears inseparable from the influence of social media on the internet. Because at this time the internet has been transformed as a need that must be met. On the internet, specially social media such us Instagram, Facebook, you-tube, and so on, it is shown how many beauty standards are currently emerging. That why society becomes indoctrinated to be able to get the predicate of beauty as everyone longs for. In this study, we wanted to find out whether the stigma regarding beauty standards, as we have mentioned above, also occurs among students of social sciences study program at this time. Our research uses descriptive qualitative methods which will describe social situations, events or events that are happening.